DNA methylation status of SERPINA3 gene involved in mRNA expression in three cattle breeds. Issue 6 (18th November 2022) - Wang, Dahui; Wen, Yifan; Zhang, Zijing; Yang, Shizhen; Liu, Xian; Cai, Cuicui; An, Qingming; Lyu, Shijie; He, Hua; Xie, Jianliang; Lei, ChuZhao; Chen, Hong; et al.
Abstract: DNA methylation could take part in the gene expression and acts an important role in muscle development. In this study, DNA methylation and expression in adipose and muscle tissues were examined at the same time to evaluate the extent of epigenetic modifications and gene expression on the differentially methylated region (DMR) in SERPINA3 . Chain reaction of bisulfite sequencing polymerase (BSP) was used to compared difference among DNA methylation patterns. The result of quantitative real-time PCR (qPCR) analysis showed that there was an extensive expression of SERPINA3 gene in tissue and there was a significant difference existing in muscle and adipose between Jiaxian cattle and individual of other breeds with increasing hybridization ( p  < 0.05). The statistic analyses indicated that DNA methylation patterns had a significant influence to the level of mRNA in tissue of fat and muscle. This study may be an important reference for investigating development of muscle tissue in cattle, and may promote the process of cattle molecular breeding.